The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1080/24740527.2022.2067032
|View full text |Cite
|
Sign up to set email alerts
|

Back and neck pain: A comparison between acute and chronic pain–related Temporomandibular Disorders

Abstract: Background Temporomandibular disorders (TMDs) are common and cause persistent pain. Comorbidities are associated with TMDs and can affect the effectiveness of their treatments. The literature is lacking enough evidence on the difference between acute and chronic pain, particularly in TMDs. Investigating this difference could highlight potential risk factors for the transition from acute to chronic pain–related TMDs. Aim To compare the likelihood of back and neck pain (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
4
0
3
Order By: Relevance
“…As clinical applicability to evidence-based practice, we suggest to the health professionals, first of all, screen fibromyalgia using specific instruments (e.g., the fibromyalgia rapid screening tool [ 41 ]). In the same way, other chronic musculoskeletal pain must be evaluated by specific instruments (respecting the cross-cultural adaptation [ 42 ]), because there are questionnaires, scales, and specific tests for low back pain [ 43 ], knee pain [ 44 ], neck pain [ 45 ], temporomandibular disorders [ 46 ], and other musculoskeletal diseases. Therefore, the WPI and SSS apply to the individuals which ACR has suggested: fibromyalgia patients [ 1 , 6 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As clinical applicability to evidence-based practice, we suggest to the health professionals, first of all, screen fibromyalgia using specific instruments (e.g., the fibromyalgia rapid screening tool [ 41 ]). In the same way, other chronic musculoskeletal pain must be evaluated by specific instruments (respecting the cross-cultural adaptation [ 42 ]), because there are questionnaires, scales, and specific tests for low back pain [ 43 ], knee pain [ 44 ], neck pain [ 45 ], temporomandibular disorders [ 46 ], and other musculoskeletal diseases. Therefore, the WPI and SSS apply to the individuals which ACR has suggested: fibromyalgia patients [ 1 , 6 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients with high grade of disability at baseline had an increased risk of developing chronic TMD, even if this risk did not reach significance ( 33 ). Finally, another study found that chronic neck pain was more prevalent in patients with chronic TMD pain and disability than acute TMD pain, suggesting that chronic disability might be involved in the transition from acute to chronic TMD pain ( 39 ). However, the factors involved in the transition from acute to chronic pain are almost unknown and much more research is needed to understand this in order to be able to prevent the transition.…”
Section: The Transition From Acute To Chronic Tmd Painmentioning
confidence: 99%
“…Painful orofacial and neck comorbidities are often associated with the TMD [ 63 ]. These coexisting conditions (particularly, headache, migraine, and neck pain) are not only highly associated with chronic pain-related TMDs but also increase the risk of their development [ 38 , 64 , 65 ]. The International Classification of Headache Disorders (ICHD) [ 66 ] and the DC/TMD [ 1 ] consider the main characteristics of pain in headaches and TMD, respectively.…”
Section: Diagnosis Of Central Sensitization In Tmdmentioning
confidence: 99%
“…There are several hypotheses attempting to explain the association between TMD and headaches, including neuronal convergence, central sensitization, and inhibition of the descending pain downregulation mechanisms [ 67 , 68 ]. The strict relationship between TMD, headaches, and neck pain has been recently evaluated, not only in terms of sharing common pathogenic mechanisms and clinical features but also considering that one condition might influence or promote the development of another [ 11 , 64 , 69 ]. These conditions can cause facial pain and are frequently associated with the development of craniofacial allodynia during painful exacerbation [ 12 ].…”
Section: Diagnosis Of Central Sensitization In Tmdmentioning
confidence: 99%